Programmable 3D Self‐Folding Structures with Strain Engineering. (21st December 2020) - Guo, Qiaohang; Pan, Yian; Lin, Junjie; Wan, Guangchao; Xu, Borui; Hua, Nengbin; Zheng, Chan; Huang, Youting; Mei, Yongfeng; Chen, Wenzhe; Chen, Zi
Abstract : 3D Self‐Folding Structures In article number 2000101, Qiaohang Guo, Zi Chen, and co‐workers use a strain engineering approach to fabricate bilayer structures across multiple length scales that can transform configuration between cylindrical and helical ribbon shapes. The mechanical principle can be applied to design and fabricate programmable and reconfigurable structures with applications in micro‐electromechanical system, energy harvesting, and flexible robotics. The cover image uses the versatile helical shapes to create a pattern of Bagua, which represents the fundamental principles of reality.